(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
Summoned to reflect on possible bridges between extension practices and ways of preserving cultural heritage, in this work we propose to rescue and analyze an experience carried out within the Cultural Academic Centre "Paco Urondo" - dependent on the Faculty of Philosophy and Letters of the University of Buenos Aires - based on a seminar on Territorialized Socio-educational Practices (PST) that we carried out during the summer bimester 2022. As an integral example between teaching, extension and research, this seminar allowed us to implement collaborative cartographies on the heritage of the chosen space, based on its urban environment; Delivering as a final product of the course a material that consisted of an audio guide to travel by metro, linking two campuses of the faculty. We maintain that the patrimonial has become a knowledge-tool for the reinforcement of shared identities, not only from the educational community, but also, a prosperous invitation to look for the city and (re)know it from other perspectives.